(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
The utilization of the existing breakwater constructions into wave energy conversion has been often adopted to rendering a revenue of the capital cost of investment. The paper has contributed to viable concept of a new integration design through more effectively capturing wave-overtopping which finally converts into electrical energy. This design is hereafter called Overtopping Breakwater for Energy Conversion (OBREC). The development of an experimental test of the current OBREC has been conducted to obtain a proper ramp shape through evaluating the amounts of the wave-overtopping discharges into the reservoir incorporated with wave-reflection coefficients. To achieve the objective, several geometry ramps such as linear, convex, concave and cubic shapes have been experimentally investigated at the National Research Institute Malaysia (NAHRIM) laboratory. The experimental study showed that the cubic-ramp shape has resulted in more significant amount of the wave-overtopping discharge into the reservoir associated with the low wave-reflection coefficient than the other ramp shapes. In general, it is merely concluded that this investigation provides very promising concept of the new proposed OBREC design to harness the larger wave energy.